Functional Janus dendrimers containing carbazole with liquid crystalline, optical and electrochemical properties. Issue 2 (26th January 2020) - Iguarbe, Verónica; Barberá, Joaquín; Serrano, José Luis
ABSTRACT: Novel liquid crystalline Janus dendrimers that combine a mesogenic block and an electroactive block have been synthesised. The mesogenic block is based on two third-generation Percec-type dendrons bearing six or eight terminal dodecyloxy alkyl chains, whereas the electroactive blocks are formed by one or two carbazole units. The liquid crystal behaviour was investigated by polarised-light optical microscopy, differential scanning microscopy and X-ray diffraction. The Janus dendrimers with one electroactive unit exhibited cubic or columnar liquid crystal phases, whereas the Janus dendrimers with two electroactive units did not show liquid crystalline behaviour. The UV-vis absorption and emission properties of the Janus dendrimers were investigated. The spectra suggested the existence of π-π stacking and the formation of aggregates in the solid state. Electrodeposition of the carbazole-containing dendrimers afforded semi-globular particles in which the number of electropolymerizable units and the flexible or rigid character of the linker have a decisive influence in the particle size. Graphical Abstract: uf0001